2005
DOI: 10.1002/uog.2592
|View full text |Cite
|
Sign up to set email alerts
|

Routine pre‐evacuation ultrasound diagnosis of hydatidiform mole: experience of more than 1000 cases from a regional referral center

Abstract: Routine pre-evacuation ultrasound examination identifies less than 50% of hydatidiform moles, the majority sonographically appearing as missed or incomplete miscarriage. Detection rates are, however, higher for complete compared to partial moles, and improve after 14 weeks' gestation. Histopathological examination of products of conception remains the current gold standard for the identification of gestational trophoblastic neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
118
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 15 publications
4
118
1
9
Order By: Relevance
“…A recent large study 3 reporting on more than 1000 cases of proven or suspected hydatidiform moles, in whom an ultrasound examination had been carried out prior to evacuation of the uterus, reported that just over 40% of cases overall were suspected on ultrasound examination, although this figure was 80% for CHMs and 30% for PHMs, which is similar to that of another recent study 4 . Furthermore, detection rates improved significantly beyond 14 weeks of gestation, compared to when the scan was carried out in the first trimester 3,5 . It remains uncertain whether those cases unsuspected following ultrasound examination represent intrinsic differences in the molar phenotype compared to cases that are detected sonographically, or whether the detection rates are simply related to sonographer expertise.…”
Section: Introductionsupporting
confidence: 72%
“…A recent large study 3 reporting on more than 1000 cases of proven or suspected hydatidiform moles, in whom an ultrasound examination had been carried out prior to evacuation of the uterus, reported that just over 40% of cases overall were suspected on ultrasound examination, although this figure was 80% for CHMs and 30% for PHMs, which is similar to that of another recent study 4 . Furthermore, detection rates improved significantly beyond 14 weeks of gestation, compared to when the scan was carried out in the first trimester 3,5 . It remains uncertain whether those cases unsuspected following ultrasound examination represent intrinsic differences in the molar phenotype compared to cases that are detected sonographically, or whether the detection rates are simply related to sonographer expertise.…”
Section: Introductionsupporting
confidence: 72%
“…The sensitivity for ultrasound diagnosis at 13 to 14 + 6 weeks was 44% compared to 13% at 7 to 12 + 6 weeks ( Figure 3). A recent retrospective analysis of the pre-evacuation ultrasound findings by Fowler et al (2006), in over 1000 women with a confirmed histological diagnosis of HM referred to a regional trophoblastic disease unit, also showed a trend towards improved detection rates beyond 14 weeks' gestation 6 . This implies that ultrasound appearances suggestive of HM are not reliably visible until towards the end of the first trimester, something that has also been reported by other authors.…”
Section: Sensitivity For Hydatidiform Molementioning
confidence: 98%
“…11,12 USS detected 40% of molar pregnancy, as most of the diagnosis was before 14 weeks; this is representative of other studies that suggest a pre-evacuation diagnosis of molar pregnancy of 35-40% before 14 weeks. 13 Majority of patients had ERPC within one week from USS suggesting possible molar pregnancy. There are no guidelines for when ERPC for possible GTD should be carried out as most GTD are diagnosed after evacuation from histology.…”
Section: Sagoo B Et Al Int J Reprod Contracept Obstet Gynecol 2015 mentioning
confidence: 99%